Probing Mixing of Photons and Axion-Like Particles by Geometric Phase - A. Capolupo; G. Lambiase; G. Vitiello (Advances in High Energy Physics)
We find that a geometric phase characterizes the phenomenon of mixing of photons with axion-like particles (ALPs). The laboratory observation of such a phase may provide a novel tool able to detect such a mixing phenomenon. We show that the geometric phase is dependent on the axion-like particle mass and coupling constant. We discuss an interferometric experiment able to detect the geometric phase associated with the ALPs-photon mixing.